Perception of the organization's safety culture by medical staff in Germany and Russia - K. N. Tsaranov (Исследования и практика в медицине)
Purpose of the study. To compare the perception of the safety culture of the organisation by medical staff in Germany and Russia.Materials and methods. In the study carried out in Germany (Bohmann F. O. et al.), the original Safety Attitudes Questionnaire (SAQ), was used. The Russian sample, an adapted and validated Russian-language version of the questionnaire was used (Tsaranov, K.N. et al.).Results. According to the indicator "Experience of work" among German medical workers, the results of the questionnaire showed higher results for all of the studied indicators except "Stress recognition" in the group of medics with more than 5 years of work experience. Among Russian medics higher results were observed in the group of respondents with less than 5 years of work experience except for the "Perceptions of management".For the indicator "professional position" among medics in Germany, the results of the questionnaire showed higher results for all of the studied indicators in the group of medics who occupy the professional position of "physician". In Russia nursing staff score higher on the "Working conditions" factor, while physicians score higher on "Teamwork climate", "Safety climate" and "Stress recognition", showed a coincidence of results on "Job satisfaction" and "Perceptions of management" scales.The neuroradiology department scores higher than the neurology department of German clinics on the factors "Teamwork climate", "Safety climate", "Job satisfaction" and "Working conditions". The coincidence with the results of the mean values in both groups is observed for the factor "Perceptions of management". Russia has the highest scores for most of the factors: "Safety climate", "Job satisfaction", "Perceptions of management" and "Working conditions" were shown by the staff in the reception and diagnostic department. Low scores were found for the factors "Teamwork climate" and "Safety climate" among staff in the infectious diseases department, and "Stress recognition" in the intensive care and combustiology departments.Conclusion. Significant differences were revealed according to the indices "length of professional experience", "professional position" and "department of work" among employees of medical clinics in Russia and Germany. The results enable the identification of target points for the design of a medical organisation development program aimed at increasing the level of evaluation of the safety culture of a medical organisation.